2021
DOI: 10.1002/lt.26353
|View full text |Cite
|
Sign up to set email alerts
|

Implications and Management of Cirrhosis‐Associated Immune Dysfunction Before and After Liver Transplantation

Abstract: Cirrhosis‐associated immune dysfunction (CAID) describes a panacea of innate and adaptive deficits that result from the sequelae of cirrhotic portal hypertension that is similar in its manifestations regardless of etiology of chronic liver injury. CAID is associated with synchronous observations of dysregulated priming of innate immune effector cells that demonstrate a proinflammatory phenotype but are functionally impaired and unable to adequately prevent invading pathogens. CAID is mainly driven by gut‐barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 159 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Patients with cirrhosis have higher levels of proinflammatory cytokines, alterations in innate immunity leading to impaired pathogen surveillance, increased bacterial translocation leading to systemic endotoxemia, and a state of chronic inflammation with decreased effectiveness to respond to and clear pathogenic insults. [41][42][43][44] All of these factors increase the risk of infection including SBP. 36,45,46…”
Section: Diagnosis Of Portal Hypertension In Childrenmentioning
confidence: 99%
“…Patients with cirrhosis have higher levels of proinflammatory cytokines, alterations in innate immunity leading to impaired pathogen surveillance, increased bacterial translocation leading to systemic endotoxemia, and a state of chronic inflammation with decreased effectiveness to respond to and clear pathogenic insults. [41][42][43][44] All of these factors increase the risk of infection including SBP. 36,45,46…”
Section: Diagnosis Of Portal Hypertension In Childrenmentioning
confidence: 99%
“…(7) BT is a signi cant driver of cirrhosis-associated immune dysfunction (CAID) which increases susceptibility to infection. (8,9) Gut microbiota manipulation with the non-absorbable antibiotic rifaximin-α in cirrhotic patients led to a reduction in hospitalisation and 30-day readmission. (10,11) Furthermore, we have recently shown that rifaximin-treated cirrhotic patients were less likely to develop infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CAID, LT amplifies the profound immunosuppressive state of patients due to major surgery, immunosuppressive drugs, and intensive care unit stay). Therefore, infections constitute a major clinical issue in pre- and post-LT patients ( Tranah et al, 2022 ). Before LT, infections in cirrhotic patients are both more frequent and more severe in association with cirrhosis severity and they can delay the access to a graft and increase mortality risk ( Finkenstedt et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Before LT, infections in cirrhotic patients are both more frequent and more severe in association with cirrhosis severity and they can delay the access to a graft and increase mortality risk ( Finkenstedt et al, 2013 ). After LT, infections increase morbidity and graft dysfunction ( Tranah et al, 2022 ). Noteworthy, infections represent the major cause of death in the first year following LT in ACLF patients ( Sundaram et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%